2020
DOI: 10.1287/mksc.2018.1128
|View full text |Cite
|
Sign up to set email alerts
|

Which Healthy Eating Nudges Work Best? A Meta-Analysis of Field Experiments

Abstract: The effectiveness of healthy eating nudges in field settings increases as they shift from focusing on influencing cognition to affect to behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
211
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(255 citation statements)
references
References 167 publications
16
211
3
4
Order By: Relevance
“…A red bar indicated carbon emissions in the relatively high range, and a green bar indicated carbon emissions in the relatively low range. Traffic light colours increase the effectiveness of carbon labels (Thøgersen & Nielsen, 2016) because they are commonly understood (Berry et al, 2008;R€ o€ os & Tj€ arnemo, 2011) and help consumers categorize food options (Cadario & Chandon, 2017).…”
Section: Stimulimentioning
confidence: 99%
“…A red bar indicated carbon emissions in the relatively high range, and a green bar indicated carbon emissions in the relatively low range. Traffic light colours increase the effectiveness of carbon labels (Thøgersen & Nielsen, 2016) because they are commonly understood (Berry et al, 2008;R€ o€ os & Tj€ arnemo, 2011) and help consumers categorize food options (Cadario & Chandon, 2017).…”
Section: Stimulimentioning
confidence: 99%
“…Behavior-based interventions may be particularly effective. A recent meta-analysis of healthy eating nudges in field settings found that effect size for what the authors termed "behaviorally oriented" nudges was over three times that of "cognitively oriented" nudges (Cadario & Chandon, 2019). This is another example of how behavior science contributes to the public welfare.…”
Section: Implications Of Behavior Sciencementioning
confidence: 99%
“…Yet, some do not see a problem here, positing that perhaps the principle of positive reinforcement discovered through decades of basic research is sufficient for application (Baer, 1981), or that ABA and EAB have speciated as a natural consequence of changing social values (Rider, 1991)-c'est la vie. Others do see a problem and propose various schemes for translational research reminiscent of Bush's (1945) expanded definition of basic research (Critchfield, 2011;Kyonka & Subramaniam, 2018;Mace & Critchfield, 2010).…”
mentioning
confidence: 99%
“…The majority of systematic reviews and meta-analyses suggest a small but positive effect of these strategic changes in altering behavior [21][22][23][24]. Since there can be many types of behavioral change interventions, analyses are typically categorized by the type of nudge.…”
Section: The Behavior Change Solutionmentioning
confidence: 99%
“…These include: cognitive-oriented nudges such as descriptive and evaluative nutritional labelling or visibility enhancements; affective-oriented nudges such as hedonic or preference enhancements or healthy eating calls; and behavior-oriented nudges that influence selection, purchase, and food consumption behaviors by changing convenience (e.g., placement) or properties (e.g., size) of the objects or stimuli (e.g., see the Typology of Interventions in Proximal Physical Micro-Environments (TIPPME) [25]. Cadario and Chandon [22] conducted a meta-analysis of nudges and found that the type of nudge that showed the largest effect was behavior-oriented nudges (such as convenience or size enhancements), followed by affective-oriented nudges (such as hedonic enhancements and healthy eating calls). The least effective nudges were cognitive-oriented interventions (such as descriptive nutritional labeling, evaluative nutritional labeling, and visibility enhancements).…”
Section: The Behavior Change Solutionmentioning
confidence: 99%